Empowering The Role Of Parents And Teachers In Surabaya Baptist Christian Elementary School - Hudi Winarso; florence pribadi; Rahajoe Imam Santosa; Angelarita Djami Raga; Glory Ta’bi Palloan (Universitas Serang Raya, 2023)
Fostering distinguished human resources need to be done since early stages. Grade 4-6 elementary students are in prepuberty group and are filled with storm and stress. Should this phase is handled properly, it would bring impact for the children’s future. This community empowerment is done with focus on grade 4-6 students at Baptis elementary school Surabaya, with target of increasing knowledge, skills for nutrition and teachers’ knowledge on sexual education in pre-puberty children. Uplifting teachers and parents’ knowledge is done by seminar and discussion, followed by practicing preparing healthy menu by parents. Results: data gathered showed increased of knowledge and skill regarding healthy nutrition and children sexual education. The community empowerment process itself is a new learning experience for the teachers in using online method as teaching delivery method.